2019
DOI: 10.1111/tpj.14364
|View full text |Cite
|
Sign up to set email alerts
|

R2R3‐MYB transcription factor MYB6 promotes anthocyanin and proanthocyanidin biosynthesis but inhibits secondary cell wall formation in Populus tomentosa

Abstract: Summary The secondary cell wall is an important carbon sink in higher plants and its biosynthesis requires coordination of metabolic fluxes in the phenylpropanoid pathway. In Arabidopsis (Arabidopsis thaliana), MYB75 and the KNOX transcription factor KNAT7 form functional complexes to regulate secondary cell wall formation in the inflorescence stem. However, the molecular mechanism by which these transcription factors control different branches of the phenylpropanoid pathway remains poorly understood in woody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 93 publications
2
89
0
Order By: Relevance
“…It has been demonstrated that the phenylpropanoid and flavonoid biosynthesis pathways are regulated by different TF classes, such as MYB, WRKY, NAC, and bHLH, through modulating the expression of the related structural genes. Among these TFs, MYB-bHLH-WD40 repeat (MBW) ternary complexes have been illustrated to be one of the most important regulatory components that are involved in phenylpropanoid and flavonoid biosynthesis [52][53][54][55][56]. To date, certain MBW component genes that regulate flavonoid biosynthesis have been identified in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the phenylpropanoid and flavonoid biosynthesis pathways are regulated by different TF classes, such as MYB, WRKY, NAC, and bHLH, through modulating the expression of the related structural genes. Among these TFs, MYB-bHLH-WD40 repeat (MBW) ternary complexes have been illustrated to be one of the most important regulatory components that are involved in phenylpropanoid and flavonoid biosynthesis [52][53][54][55][56]. To date, certain MBW component genes that regulate flavonoid biosynthesis have been identified in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…The MYB TF (EUC13670) and bHLH (EUC04483) were supposed to regulated anthocyanin synthesis in H12 leaves. Wang reported R2R3-MYB TF MYB6 of Populus tomentosa was mainly expressed in young leaves and the overexpression of MYB6 in transgenic poplar resulted in the signi cant up-regulation of anthocyanin and procyanidin accumulation [32]. In addition, PpGST together with PpMYB10.1 might regulate the anthocyanin accumulation [33].…”
Section: Structural Genes and Transcription Factors Involved In Anthomentioning
confidence: 99%
“…TFs are also powerful targets for manipulating secondary metabolic pathways in plants (Cao et al 2018;Huang et al 2019;Wang et al 2019aWang et al , 2019b. However, little is known about the regulatory mechanisms or target genes of TFs involved in the phenolic acid biosynthesis pathway in S. miltiorrhiza.…”
Section: Introductionmentioning
confidence: 99%
“…MYB proteins comprise a huge family of TFs that play important roles in plant development and secondary metabolism (Borevitz et al 2000;Czemmel et al 2012;Chen et al 2019;Hao et al 2020). MYB TFs are classified into four subfamilies based on the number of conserved MYB domains in their N-terminal regions, 1R-MYB, R2R3-MYB, R1R2R3-MYB, and 4R-MYB TFs, with R2R3-MYBs representing the major subfamily in plants (Rosinski and Atchley 1998;Dubos et al 2010;An et al 2015;Wang et al 2019aWang et al , 2019bHao et al 2020). For example, NtMYB3 represses flavonol biosynthesis in Narcissus tazetta (Anwar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation